Evaluation of antibiotic treatment decisions in pediatric intensive care units in Saudi Arabia: A national survey. Issue 9 (September 2021) - Kazzaz, Yasser M.; Alharbi, Musaed; Nöel, Kim C.; Quach, Caroline; Willson, Douglas F.; Gilfoyle, Elaine; McNally, James D.; O'Donnell, Shauna; Papenburg, Jesse; Lacroix, Jacques; Fontela, Patricia S.
Abstract: Objective: To describe variables used by Saudi pediatric intensivists to make antibiotic-related decisions for children with suspected severe bacterial infections. Methods: We conducted a cross-sectional survey, which was developed using a multi-step methodological approach. The survey included 4 clinical scenarios of the most relevant bacterial infections in pediatric critical care (pneumonia, sepsis, meningitis and intra-abdominal infection). The potential determinants of antibiotic treatment duration addressed in all scenarios included clinical variables (patient characteristics, disease severity), laboratory infection markers, radiologic findings, and pathogens. Results: The response rate was 65% (55/85). Eight variables (immunodeficiency, 3 months of age, 2 or more organ dysfunctions, Pediatric Risk of Mortality III score >10, leukocytosis, elevated C-reactive protein [CRP], elevated erythrocyte sedimentation rate [ESR], and elevated procalcitonin [PCT]) were associated with prolonging antibiotic treatment duration for all 4 clinical scenarios, with a median increase ranging from 3.0 days (95% confidence interval [CI] 0.5, 3.5, leukocytosis) to 8.8 days (95% CI 5.5, 10.5, immunodeficiency). There were no variables that were consistently associated with shortening antibiotic duration across all scenarios. Lastly, the proportion of physicians who would continue antibiotics for ≥5 days despite a positive viral polymerase chain reaction test result was 67% for pneumonia, 85% for sepsis, 63% for meningitis, and 95% for intra-abdominal infections. Conclusion: Antibiotic-related decisions for critically ill patients are complex and depend on several factors. Saudi pediatric intensivists will use prolonged courses of antibiotics for younger patients, patients with severe clinical picture, and patients with persistently elevated laboratory markers and hospital acquired infections, even when current literature and guidelines do not suggest such practices. Antimicrobial stewardship programs should include interventions to address these misconceptions to ensure the rational use of antibiotics in pediatric intensive care units.